An Online Monocular Camera-IMU Calibration Method with Structural Feature Constraints - Liao, Yunmao; Fang, Chao (International Journal of Computer Science and Information Technology, 2024)
Spatial configuration and time synchronization technology are the key to achieve high precision positioning of visual inertial system. The premise is to calibrate the internal and external parameters of the camera, the IMU (inertial measurement unit) bias and the external parameters between the camera and the IMU. In the traditional calibration method, the work of external parameter calibration is carried out offline, and it is generally completed in the initialization stage before being put into use, and it is assumed that the external parameters of each sensor will not change during the long-term operation. However, in complex practical working environments, sensor suites consisting of cameras and low-cost IMU often have time delay problems due to device processes, and visual inertia systems may be subjected to physical shocks from outside. Therefore, it is often necessary to face the failure of initial external parameters due to uncertain factors such as external shocks, time delays, mechanical structure adjustments or cumulative deformation under long-term work. In view of the above background, this paper constructs an online calibration model of monocular IMU based on the feature that the online calibration method can correct the external parameter deviation in real time and the constraint factor of the natural environment. Firstly, the external parameters of monocular camera and IMU are initialized based on physical space constraints, and the initial values to be optimized are obtained. Finally, the problem of matching the structural features in the online calibration process is solved by using the method of matching the structural features in the vertical main direction, and the objective optimization function of reprojection error considering the point and structure line is constructed. The Jacobian matrix of the reprojection error is given, and the decreasing direction of the optimization function is determined. The global optimal solution of the external parameters of camera and IMU is obtained in the online calibration.